2017
DOI: 10.1021/acs.jafc.6b02945
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Hydroxytyrosol in Experimental Diabetes Mellitus

Abstract: The aim of the study was to analyze the possible neuroprotective effect of hydroxytyrosol (HT) in diabetic animals in a model of hypoxia-reoxygenation. Rats (10 animals/group) were distributed in five groups: nondiabetic rats, control diabetic rats (DR), and DR rats treated for 2 months with 1, 5, or 10 mg/kg/day po HT. At the end of follow-up, an experimental model of hypoxia-reoxygenation in brain slices was tested. The DR group showed increased cell death, oxidative and nitrosative stress, and an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 27 publications
4
33
0
Order By: Relevance
“…Based on these grounds, diverse HT derivatives have been synthesized. [18][19][20][21][22] The bioactivities of these HT derivatives have been studied, including their antiplatelet aggregation capacity, 4,42,43 neuroprotective activity, 44 DNA oxidative damage protection, 30 cytoprotection, 45 antiinflammatory effects, 38,46 and anticancer activity. 12,47 Most of these derivatives have shown to maintain or even improve the diverse activities of free HT, mainly due to the better lipophilic/hydrophilic balance exhibited by these derivatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these grounds, diverse HT derivatives have been synthesized. [18][19][20][21][22] The bioactivities of these HT derivatives have been studied, including their antiplatelet aggregation capacity, 4,42,43 neuroprotective activity, 44 DNA oxidative damage protection, 30 cytoprotection, 45 antiinflammatory effects, 38,46 and anticancer activity. 12,47 Most of these derivatives have shown to maintain or even improve the diverse activities of free HT, mainly due to the better lipophilic/hydrophilic balance exhibited by these derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…2 In the last years, scientific evidence has accumulated pointing to the pleiotropic effects of HT on multiple targets. In fact, demonstrated beneficial effects of HT for human health include its antidiabetic, 3,4 antifungal, 5 antiinflammatory, 6 antiparasitic, 7 cardio- 8 and neuroprotective 9 activities. HT has also beneficial effects on metabolic syndrome 10 and antitumoral effects of HT have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…HTyr demonstrates hypoglycemic activity in various diabetic animal models by influencing the major biochemical processes leading to diabetic vasculopathy [67,68]. An animal model experiments showed that HTyr could effectively prevent diabetic neuropathy [69,70]. It was shown that HTyr improves insulin sensitivity and restores proper insulin-signaling [71].…”
Section: Hydroxytyrosolmentioning
confidence: 99%
“…It was concluded that HT may attenuate the vasculopathy or blood vessel inflammation induced by diabetes. Reyes et al (2017) administered HT to male Wistar rats via gavage at dosages of 1, 5 or 10 mg/kg for 7 days before inducing diabetes with intravenous STZ (50 mg/kg) [60]. HT treatments continued for 2 months following the induction of diabetes.…”
Section: In Vivo Evidence: Antidiabetic Effect Of Hydroxytyrosolmentioning
confidence: 99%